Formation and dynamics of aroma compounds during manufacturing-ripening of Bouhezza goat cheese. (June 2022) - Senoussi, Asma; Rapisarda, Teresa; Schadt, Iris; Chenchouni, Haroun; Saoudi, Zineddine; Senoussi, Sana; Aissaoui Zitoun, Ouarda; Zidoune, Mohammed Nasreddine; Carpino, Stefania
Abstract: The aromatic profile development of Bouhezza goat cheese during manufacturing-ripening in traditional goatskin bags was assessed using solid-phase microextraction (SPME) and steam distillation (SD) coupled to gas chromatography-olfactometry. Sixty different odour-active compounds (OACs) were revealed. The volatile profile of Bouhezza goat cheese changed during cheese ripening, but ester and terpene compounds dominated throughout manufacturing-ripening. During ripening the number of alcohols, esters, heterocyclic compounds, ketones, sulphurs, terpenes and tiazole increased gradually. Cheese aroma results differed between the extraction methods; thiazole and sulphurs were better extracted by SPME, but heterocyclic compounds were exclusively extracted using SD. SD revealed a more complete volatile and aromatic profile of Bouhezza compared with SPME; however, the low level of common OACs showed that the methods are complementary to each other and SPME cannot be neglected. The application of different extraction methods helps to achieve a complete description of the aromatic profile of traditional cheeses.